Impacts of COVID-19 on Firms in Malaysia : Results from the 2nd Round of COVID-19 Business Pulse Survey - Kuriakose, Smita (World Bank, Washington, DC, 2021)
The re-imposition of the Conditional Movement Control Order during mid-October 2020 and the upgrade to a stricter lockdown to Movement Control Order in January 2021 has substantially weakened the recovery momentum highlighted in Round 1 of Business Pulse Survey (early October 2020). To adapt to the latest lockdown, the majority of firms responded by remaining partially open in operations. Employment adjustments such as reducing work hours remain the most common method by firms. Supply chain disruptions remain a major problem in the market. Adoption of digital technologies remains the most popular choice for adjustment by firms, with sales and marketing functions topping the list of digital adoption.